Expression of 5-lipoxygenase and leukotriene A(4) hydrolase in human atherosclerotic lesions correlates with symptoms of plaque instability - Qiu, Hong (National Academy of Sciences, 2006)
Leukotrienes (LT) are a group of proinflammatory lipid mediators that are implicated in the pathogenesis and progression of atherosclerosis. Here we report that mRNA levels for the three key proteins in LTB(4) biosynthesis, namely 5-lipoxygenase (5-LO), 5-LO-activating protein (FLAP), and LTA(4) hydrolase (LTA4H), are significantly increased in human atherosclerotic plaque (n = 72) as compared with healthy controls (n = 6). Neither LTC(4) synthase nor any of the LT receptors exhibits significantly increased mRNA levels. Immunohistochemical staining revealed abundant expression of 5-LO, FLAP, and LTA4H protein, colocalizing in macrophages of intimal lesions. Human lesion tissue converts arachidonic acid into significant amounts of LTB(4), and a selective, tight-binding LTA4H inhibitor can block this activity. Furthermore, expression of 5-LO and LTA4H, but not FLAP, is increased in patients with recent or ongoing symptoms of plaque instability, and medication with warfarin correlates with increased levels of FLAP mRNA. In contrast to human plaques, levels of 5-LO mRNA are not significantly increased in plaque tissues from two atherosclerosis-prone mouse strains, and mouse plaques exhibit segregated cellular expression of LTA4H and 5-LO as well as strong increases of CysLT(1) and CysLT(2) mRNA. These discrepancies indicate that phenotypic changes in the synthesis and action of LT in specific mouse models of atherosclerosis should be cautiously translated into human pathology. The abundant expression of LTA4H and correlation with plaque instability identify LTA4H as a potential target for pharmacological intervention in treatment of human atherosclerosis.